Clinical Presentation and Histological Variation of Pleomorphic Adenoma of Salivary Glands - Khandker, Md Nazmul Hasan; Sadat, SM Anwar; Rahman, Tarin; Haider, Ismat Ara; Ahmed, Mohiuddin (Journal of Bangladesh College of Physicians and Surgeons, 2019)
Background: Pleomorphic Adenoma is the most common salivary gland tumour accounts 40-70% of all salivary gland tumour and about 60-80% of the benign tumours and 60- 70% of all parotid tumours. There is no study conducted in Bangladesh to observe the clinical and histological variation of the tumour. This study presents 36 cases of Pleomorphic adenoma collected over 11 months at the different territory hospital of Dhaka city. Design: Observational study (November’ 2011 to September’ 2012) Setting: Department of Oral and Maxillofacial Surgery (Dhaka Dental College and Hospital, Bangabandhu Sheikh Mujib Medical Universityl), Department of ENT and Head- Neck Surgery (Dhaka Medical College and Hospital, Bangabandhu Sheikh Mujib Medical University). Method: The entire patient clinically and cytologically diagnosed as Pleomorphic adenoma were selected. Data were collected in a summarized data sheet. Then histopathological types of them were analyzed from excisional biopsized tissue. Result: There were 36 patients of Pleomorphic adenoma of which 24(66.67%) in Parotid glands, 4(11.11%) in Submandibular glands and 8(22.22%) in minor salivary glands. Among the respondents, female was predominant 20(55.56%) with ages were between 29 years to 65 years old (mean age 44.83 ± 8.32 years) with most patients (44.44%) in 41 to 50 years of life. In histophathological study showed Stromal rich 38.89%, cell rich 36.11% and classic 25%. Cuboidal cells were the most commonly found cellular type followed by plasmacytoid and spindle.Trabeculae and duct like structures were the most frequent pattern by the epithelial cells.Myxoid and Hyalinization were the most frequently found mesenchymal like tissue.Cases presented with symptoms such as swelling (100%), limitation of mouth opening, paesthesia and pain. Conclusion: The knowledge about clinical presentation and the immense variety of cells, architectures and morphological characteristics present in Pleomorphic adenoma of the salivary gland is essential for correct diagnosis and prognosis. The need for improved diagnostic facilities and upgrading of infrastructure was stressed. J Bangladesh Coll Phys Surg 2019; 37(2): 72-77